Section optimization design of UHPC beam bridges based on improved particle swarm optimization - Li, Beian; Li, Yongsi; Liu, Xiang; Liu, Xianlin; Zhu, Siwen; Ke, Lu (Frontiers in Materials, 2023)
As a new type of cement-based composite material, ultra-high performance concrete (UHPC) has excellent mechanical properties such as ultra-high strength and high durability, and has broad application prospects in the field of bridge engineering. To make full use of the superior mechanical properties of UHPC and reduce the cost of the bridge, the particle swarm optimization algorithm is used to optimize the structural design of the UHPC beam bridge; Aiming at the problem that the traditional particle swarm optimization algorithm is easy to fall into local optimum, the nonlinear adaptive weight update method is used to improve the particle swarm optimization algorithm. Based on the above-mentioned improved particle swarm optimization algorithm, the optimal design method of ordinary reinforced UHPC beams and prestressed UHPC beams with commonly used highway spans is studied. The reliability of the optimized structural limit state is analyzed by Monte Carlo (MC) importance sampling method. The results show that compared with the traditional particle swarm optimization algorithm, the improved particle swarm optimization algorithm has higher convergence speed and convergence accuracy. For ordinary reinforced UHPC beams, the main factors affecting the optimization results are the flexural capacity and crack width constraints; For prestressed UHPC beams, the main factors affecting the optimization results are the flexural capacity and deflection constraints.